Legalisation of Liquor Under the Guise of Investment Threatens Indonesia's Future on Tafsir Al-Qurṭubī Perspective - Hasibuan, Yusuf Firdaus; Fatkhurrohman, Abdul Azis (QOF, 2024)
Despite its health hazards and public debate, the liquor industry continues to innovate and grow. Indonesia seeks to balance economic investment and public safety regarding the liquor industry based on local culture and wisdom. This article aims to demonstrate the Qur'an’s normative stance on liquor through al-Qurṭubī’s legal exegesis in considering the profit and loss of liquor investment in Indonesia. The article employs a qualitative research method by utilising a semantic and content analysis approach to explore the discussion topic. The investigation focuses on the interpretation of sakar and khamar through the explanations outlined in the tafsir al- Qurṭubī, al-Jāmi' li Ahkām al- Qur'ān volumes 1, 3, 6, and 17, in addition to various relevant academic works. The research shows that liquor is harmful to consumers and not in line with Indonesian culture in general for the safety of Indonesia's generations. This article contributes to the science of Qur'anic exegesis integrated with social science and public policy that highlights the importance of philosophical, sociological, and human rights considerations in economic and public health policies.